ASSESSMENT OF BIOLOGICAL RISKS IN INFECTIOUS DISEASES TO ENSURE BIOLOGICAL SAFETY - Myrzakhmetova, B.Sh.; Zhapparova, G.A.; Tlenchiyeva, T.M.; Bissenbayeva, K.B.; Tussipova, A.A.; Zhugunissov, K.D.; Kutumbetov, L.B. (Eurasian Journal of Applied Biotechnology, 2024)
The territory of the Republic of Kazakhstan is unfavorable for a number of infectious diseases of animals and humans that pose an enzootic biological threat. Such nosological units include anthrax, blackleg, rabies, leukemia, brucellosis, tuberculosis, pasteurellosis, sheep pox, camel pox, CCHF, highly pathogenic avian influenza, foot-and-mouth disease, tick-borne encephalitis, influenza A and B, infectious hepatitis, Newcastle disease, seasonal flu, coronavirus infection COVID-19, etc., some of which affect only animals or humans, and some affect both animals and humans. While some of these diseases are natural focal and pose a constant biological threat, others appear from time to time, penetrating from neighboring countries or develop as a result of movement from the wild - reservoirs and hidden carriers of pathogens. A number of exotic diseases pose a real threat of penetration from outside the country due to interstate movements of people, animals, feed and animal products.